2015
DOI: 10.3390/v7122961
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity and Immune Evasion by Enterovirus 71

Abstract: Enterovirus 71 (EV71) is a major infectious disease affecting millions of people worldwide and it is the main etiological agent for outbreaks of hand foot and mouth disease (HFMD). Infection is often associated with severe gastroenterological, pulmonary, and neurological diseases that are most prevalent in children. Currently, no effective vaccine or antiviral drugs exist against EV71 infection. A lack of knowledge on the molecular mechanisms of EV71 infection in the host and the virus-host interactions is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 113 publications
1
80
0
Order By: Relevance
“…Excessive pro‐inflammatory chemokine and cytokine responses contribute to the EV71 infection severity. Also, this infection does not promote IFN‐I production . Ho and colleagues showed that EV71 infection‐promoted miR‐146a expression leads to suppress IFN production through inhibition of TRAF6 and IRAK1, two key factors implicated in TLR signaling pathways and IFN production .…”
Section: Exosomal Mir‐146a In Viral Infectionmentioning
confidence: 99%
“…Excessive pro‐inflammatory chemokine and cytokine responses contribute to the EV71 infection severity. Also, this infection does not promote IFN‐I production . Ho and colleagues showed that EV71 infection‐promoted miR‐146a expression leads to suppress IFN production through inhibition of TRAF6 and IRAK1, two key factors implicated in TLR signaling pathways and IFN production .…”
Section: Exosomal Mir‐146a In Viral Infectionmentioning
confidence: 99%
“…EV71 causes HFMD, neurological complications or even fatal diseases in young children and infants [5,8]. Its pathogenicity is likely related to its ability to evade host innate immunity [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…These IFNs are essential in the early control of virus infection as they facilitate the induction of over 300 ISGs that degrade viral RNAs and induce apoptosis, resulting in an antiviral state in the microenvironment [8,9]. Previous studies showed that type I IFN had a protective role in EV71 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations